It's not fair! - Sommer, Carl, 1930-; Budwine, Greg (Houston, TX : Advance Pub., 2003)
Buzzie becomes unhappy with her role as a worker bee and starts a revolt at her hive, until she discovers that working together is the best way to be happy.
"Fun times with citizenship/teamwork/responsibility"--Cover.
"Grades 1-4"--Dust jacket flap.
Keywords: Bumblebees -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Bumblebees -- Fiction; Cooperativeness -- Fiction